A Microwave Signal Generation Technique Based on Brillouin-Erbium Fiber Laser - Ahmad, Nurul Atiqah Bt; Dahlan, Samsul Haimi; Jamaluddin, Mohd Haizal; Sanchez-Lara, Rafael; Cholan, Noran Azizan (International Journal of Integrated Engineering, 2019)
An all-optical microwave signal generator based on multiwavelength Brillouin-Erbium fiber laser (MBEFL) is proposed. The MBEFL unit is designed at fixed wavelength spacing of 0.084 nm, which corresponds to 10 GHz carrier signal. The underlying mechanism MBEFL unit is by recycling the backscattered Stokes waves into the cavity to generate higher-order Stokes waves. Heterodyning process is then applied to the Brillouin pump (BP) consisted of first-order Brillouin Stokes (BS1) (0.084 nm spacing) and second-order Brillouin Stokes (BS2) (0.168 nm spacing) signals by using a photodetector (PD). The heterodyned outputs are microwave signals at the frequencies of 10.56 GHz and 21.2 GHz, relative to first order and second order Stokes waves, respectively. These microwave signals are experimentally achieved by controlling the EDF pump power where the EDF pump power can be as low as 20 mW.